Comments on Shan and Walter: ‘Towards a Set of Design Principles for Executive Compensation Contracts’ - Beaumont, Stacey; Reeb, David; Boyle, Glenn; Brown, Philip; Szimayer, Alexander; da Silva Rosa, Raymond; Hillier, David; McColgan, Patrick; Tsekeris, Athanasios; Howieson, Bryan; Matolcsy, Zoltan; Spiropoulos, Helen; et al. (Wiley, 2016)
Comment by Stacey Beaumont, Raluca Ratiu, and David Reeb: Is Ceo Pay High? CEO pay engenders substantial discussion in the popular press and among academics. The business press routinely contends that greedy and unethical CEOs obtain ‘gargantuan packages’ from ‘rubberstamping’ boards (MacDonald and Hughes, 2011, p. 233). Regulators and government officials often observe that CEOs make several hundred times the wage of the average worker and describe this as outrageous and immoral (Owen, 2009). Academic discussions often fall into two distinct categories. One category often focuses on managerial dominance or control of public firms. This managerial dominance group typically indicates that CEOs pervert the pay-setting process, enabling them to extract rents and therefore reward themselves with high compensation (e.g., Bebchuk and Fried, 2003). In contrast, the alternate group, the efficient contracting category, provides a rare talent hypothesis (e.g., Gabaix and Landier, 2008). This group posits that CEO ability represents an atypical skillset, leading to high pay in a competitive job market. Regardless of the underlying economic model of CEO pay, both groups agree that CEO pay is high.
Keywords: 53 Ciencias Económicas::5311 Organización y dirección de empresas; ODS 8 - Trabajo decente y crecimiento económico